Environment - Raven, Peter H.; Berg, Linda Ruth , 1947-; Hassenzahl, David M. (Singapore : John Wiley & Sons, 2013)
Theeight edition of Environment builds on the previous comprehensive, systems-based environmental science issue with more in-depth information on systems approach, which emphasizes the interconnected nature of environmental science throughout the text
1. Introducing environmental science and sustainability -- 2. Environmental laws, economics, and ethics -- 3. Ecosystems and energy -- 4. Ecosystems and the physical environment -- 5. Ecosystems and living organisms -- 6. Major ecosystems of the world -- 7. Human health and environmental toxicology -- 8. The human population -- 9. The urban environment -- 10. Energy consumption -- 11. Fossil fuels -- 12. Renewable energy and nuclear power -- 13. Water : a limited resource -- 14. Soil resources -- 15. Mineral resources -- 16. Biological resources -- 17. Land resources -- 18. Food resources -- 19. Air pollution -- 20. Global climate change -- 21. Water pollution -- 22. Pest management -- 23. Solid and hazardous wastes -- 24. Tomorrow's world
Includes index
Keywords: Conservation of natural resources; Environmental education; Environmental policy